2021
DOI: 10.1055/s-0041-1725096
|View full text |Cite
|
Sign up to set email alerts
|

Fibrinolytic Alterations in Sepsis: Biomarkers and Future Treatment Targets

Abstract: Sepsis is a life-threatening condition which develops as a dysregulated immune response in the face of infection and which is associated with profound hemostatic disturbances and in the most extreme cases disseminated intravascular coagulation (DIC). In addition, the fibrinolytic system is subject to alterations during infection and sepsis, and impaired fibrinolysis is currently considered a key player in sepsis-related microthrombus formation and DIC. However, we still lack reliable biomarkers to assess fibri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 14 publications
(22 citation statements)
references
References 138 publications
2
20
0
Order By: Relevance
“…Septic shock patients are at high risk of developing coagulation disturbances, which, in their most severe form, may manifest as disseminated intravascular coagulation (DIC), a life-threatening condition [1,2]. Altered fibrinolysis is recognised as a contributor to sepsis-related coagulopathy and may aggravate microthrombus formation, organ failure and mortality [3][4][5]. Sepsis patients are generally considered to have impaired fibrinolysis [3,4]; however, recent literature indicates that some patients with sepsis-related DIC have decreased fibrin formation capacity [6] and even enhanced clot susceptibility to lysis [7], and hypocoagulability in sepsis has been associated with poor prognosis [8].…”
Section: Introductionmentioning
confidence: 99%
“…Septic shock patients are at high risk of developing coagulation disturbances, which, in their most severe form, may manifest as disseminated intravascular coagulation (DIC), a life-threatening condition [1,2]. Altered fibrinolysis is recognised as a contributor to sepsis-related coagulopathy and may aggravate microthrombus formation, organ failure and mortality [3][4][5]. Sepsis patients are generally considered to have impaired fibrinolysis [3,4]; however, recent literature indicates that some patients with sepsis-related DIC have decreased fibrin formation capacity [6] and even enhanced clot susceptibility to lysis [7], and hypocoagulability in sepsis has been associated with poor prognosis [8].…”
Section: Introductionmentioning
confidence: 99%
“…39 Yet, ROTEM/TEG might be limited providing detailed analysis of changes in fibrinolysis induced by cytoreductive surgery with HIPEC. 54,55 Elevated PAI-1, indicating suppressed fibrinolysis, was reported after cytoreductive surgery with HIPEC in the study by Delhorme et al 41 Additionally, the authors reported significantly in-creased PAI-1 at postoperative day 5 in patients with postoperative bleeding complications following cytoreductive surgery with HIPEC with oxaliplatin. 41 However, fibrinolysis was sparsely investigated and no consistent effect of cytoreductive surgery with HIPEC on fibrinolysis was found.…”
Section: Discussionmentioning
confidence: 94%
“…Although there was some heterogeneity in the study population, dogs with sepsis were hypercoagulable and hypofibrinolytic relative to normal dogs. Depressed fibrinolysis combined with increased fibrinogen thus contributes to a prothrombotic risk in dogs with sepsis, as it does in humans ( 46 , 47 ). Our results support recommendations that sepsis represents a risk factor for thrombosis in dogs that can warrant thromboprophylaxis ( 48 , 49 ).…”
Section: Discussionmentioning
confidence: 99%